Establishment of safety paradigms and trust in emerging adult relationships. Issue 8 (2nd August 2016) - Mullinax, Margo; Sanders, Stephanie; Higgins, Jenny; Dennis, Barbara; Reece, Michael; Fortenberry, J. Dennis
Abstract: There is a critical need to understand the interplay between relationship trust and public health outcomes. The purpose of this study was to develop an understanding of emerging adult women's processes of establishing trust in sexual relationships. Twenty-five women aged 18–24 years participated in semi-structured interviews. Throughout the interviews, women compared and contrasted experiences in which they felt comfortable engaging in sexual intercourse with a partner versus times in which they did not feel comfortable. Analysis was based on a critical qualitative research orientation. When asked to speak to instances when they felt comfortable having sex, most women spoke about relationship trust. Many participants conceptualised trust based on past experiences with bad relationships or sexual violence. Based on their previous experiences of feeling unsafe or undervalued, emotional and physical security became prioritised in relationship development. Trust was developed through friendship, communication over time, and through shared life experiences. This research is among the first to qualitatively investigate trust formation and other impersonal dynamics related to sexual health decision-making. Insights from this study should be translated into future action by public health practitioners to promote healthy sexual relationships and communication about sexual health topics as a form of trust building.